Tracing the Cascade of Children's Insecurity in the Interparental Relationship: The Role of Stage‐Salient Tasks. Issue 1 (23rd August 2012) - Davies, Patrick T.; Manning, Liviah G.; Cicchetti, Dante
<x xml:space="preserve">Abstract</x> This study examined whether children's difficulties with stage‐salient tasks served as an explanatory mechanism in the pathway between their insecurity in the interparental relationship and their disruptive behavior problems. Using a multimethod, multi‐informant design, 201 two‐year‐old children and their mothers participated in 3 annual measurement occasions. Structural equation modeling analyses indicated that coder ratings of children's insecure responses to interparental conflict from a maternal interview predicted observer ratings of their difficulties with stage‐salient tasks (i.e., emotion regulation, autonomy, resourceful problem solving) 1 year later after controlling for initial stage‐salient task performance. Stage‐salient task difficulties, in turn, predicted experimenter reports of children's behavior problems 1 year later. Associations remained robust in the broader context of other pathways hypothesized in prevailing developmental cascade models.